Radial and axial variation of fiber and vessel element length in Nothofagus nervosa (Nothofagaceae) of Patagonia Argentina - Medina, Andrea A.; Dionisio, Natalia M.; Laffitte, Lorena N.; Andía, Ismael R.; Rivera, Stella M. (Instituto de Ecología, A.C., 2013)
The goal of this paper was to characterize fibers and vessel elements in the wood of Nothofagusnervosa (Phil.) Dim. et Mil., Nothofagaceae, (raulí), determining the variation of their lengths in the treein radial and axial orientations and evaluating their variability between trees. Four trees with DBH (diameterat breast height) above 40 cm were used from Quilanlahue site, Neuquén, Argentina, from whichsections were removed at three different heights. The north radius of each section was used and microscopicpreparations and macerations were produced every ten years from pith to bark. The characteristicsof fibers and vessel elements were described. The length of both cells was significantly greater inradial orientation from pith to bark. In axial orientation the length of the fiber is variable, while the lengthof vessel elements does not show significant changes. The greatest source of variation was observedin the tree related to the different ages at which wood was formed. A diminishing in the variation coefficientwas observed for the length of fibers and vascular elements from twenty years of age of the tree.Variability among trees was not significant.